Promoting students' tolerance awareness in the context of peace education through Wayang Golek - Harjianto, Feri Henri; Handarini, Dany Moenindyah; Setiyowati, Arbin Janu (ProGCouns: Journal of Professionals in Guidance and Counseling, 2021)
Tolerance awareness is one of important aspect to realizing peace education that train students to avoid of using violence. This study aims to represent the results of the tolerance awareness training guide using "wayang golek" as a media to realize peace education by using indigenous heritage that has been tested for acceptability standards.  Research and development model used in this study which has been modified according to the needs and deficiency of researchers in the field, so that it consists of six stages: preliminary study, planning, product making, product testing, product revision, and final product. The assessment that used in this study was adjusted to "Standards for Evaluation of Educational Programs, Projects, and Materials by the joint committee" which involves two experts in the field of guidance and counseling as well as practitioners in the field. The result shows that the guide of tolerance awareness training using "wayang golek" as a media fulfilling the acceptability standards. Recommendation for further researchers to test the effectiveness of the product using experimental method.